Implementasi Nilai-Nilai Pancasila di Kalangan Generasi Milenial Melalui Media Sosial - Amanda Selviana; Emilia Susanti; Julia Elvina; Iis Sholehah; Layyana Syarifah Pane; Putri Diana (Pusat Riset dan Inovasi Nasional, 2024)
The acceptance of Pancasila values by the millennial generation on social media has an impact on Indonesian national identity, as this essay explores. The millennial generation makes a substantial contribution to strengthening national identity through volunteering on social and environmental concerns, creating online communities, and using social media. The principles of Pancasila, which include justice, democracy, unity, divinity, and humanity, serve as the foundation for this approach. Social media can have bad effects like addiction and overconsumption, but it can also be a helpful tool for promoting causes like environmental sustainability and gender equality. Thus, the millennial generation should embrace Pancasila ideals on social media in order to raise awareness of the richness and diversity of Indonesian culture.